User acceptance studies for LED office lighting: Preference, naturalness and colourfulness. (February 2015) - Dangol, R; Islam, MS; Hyvärinen, M; Bhushal, P; Puolakka, M; Halonen, L
Two mock-up office rooms, one with a spectrally tuneable LED lighting system and the other with a fluorescent lamp (FL) lighting system were built for user acceptance studies for office lighting. One room was illuminated with six LED luminaires and the other with six FL luminaires. Each LED luminaire has 480 LEDs (20 different LED types and 24 of each type). Each FL luminaire has eight fluorescent lamps, four with a correlated colour temperature of 4000 K and four of 6500 K. User acceptance studies in the office environments were conducted with 40 observers, each observer having 16 sessions (six LED spectral power distributions (SPDs) + two FL SPDs and two illuminances (500 lux and 300 lux)). The observers performed office-related tasks while being totally immersed in one of these lighting conditions. The objective of this study was to verify previous results obtained in small-scale booth experiments and to further study peoples' preferences for LED office lighting. The small-scale experiments showed that LEDs with a higher value of reference-based colour metrics (such as colour quality scale (CQS) colour preference scale) and with a higher value of area-based or volume-based metrics (such as CQS gamut area scale or gamut area index) were preferred by the observers. The office room study of the present work validated the findings of the earlier experiments but now in an office lighting environment. Furthermore, the observers preferred 4000 K to 6500 K at a light level of 500 lux and the light level of 500 lux over 300 lux. It was also found that the simplest LED SPD with three peaks has similar colour quality characteristics to complex LED SPDs with several peaks.